Cross-cultural COVID-19 conspiracy thinking and religious, spiritual, and supernatural variables: a systematic review - Pait, Kathleen C. (Religion, brain & behavior, 2025)
This systematic review examined the relationship between COVID-19 conspiracy thinking and religious, spiritual, and supernatural beliefs and practices (referred to here as religious/spiritual/supernatural (r/s/s) variables). Searches were conducted among PubMed, PLoS One, PsycNet, Cochrane Library, and university library databases and examined 25 studies from 17 countries published between January 2020-December 2022. The results revealed nuanced findings. In some cultures, religiosity was positively associated with COVID-19 conspiracy thinking. In Poland, religious fundamentalism was positively linked with COVID-19 conspiracy thinking, but centrality of religion was not. Religiosity and COVID-19 conspiracy thinking were positively related to vaccine hesitancy in four studies. However, religious vaccination beliefs related to God and to divine protection were positively associated with vaccine acceptance. Similarly, believing that God drove people to create COVID-19 vaccines was negatively related to COVID-19 conspiracy beliefs. Spiritual eco-awareness was positively associated with COVID-19 conspiracy thinking in a European sample, but spiritual relatedness was not. Although some results are consistent with previous literature, the relationship between conspiracy thinking and r/s/s variables is clearly more complex. Further research is needed to understand the dimensions of r/s/s/ variables that drive this relationship, and that may also serve to protect people from conspiracy thinking.